Carpal Tunnel Syndrome: A Randomized Comparative Study of Magnetic Field Therapy and Ultrasound Therapy - Farooq Khaleel, Raed; Basim Al Khafajy, Mohammed (Diyala Journal of Medicine, 2024)
Background: Carpal tunnel syndrome is a frequently observed condition affecting the wrists and fingers, characterized by numbness, tingling, and sometimes pain. Objective: To evaluate and compare the efficiency of magnetic field therapy and ultrasound therapy in rehabilitating women with carpal tunnel syndrome (CTS). Patients and Methods: Forty women with mild to moderate CTS were included in the study, and an electromyography (EMG) and examination confirmed the diagnosis. The participants were assigned into two groups. Group A received magnetic field therapy, and Group B received ultrasound therapy. Patients for each group received a six-session clinical evaluation. The outcomes included the Boston Carpal Tunnel Syndrome Questionnaire (BCTSQ), handgrip strength, wrist joint movements (flexion and extension), as well as the Visual Analogue Scale (VAS). Results: The paired t-test analyses demonstrate a significant improvement in the Boston questionnaire and VAS in both intervention groups at a P-value ≤0.05. The independent sample t-test analysis for post-intervention for both groups showed superiority for magnetic field therapy; no significant differences were observed in the improvement of wrist movement (Flexion = 0.66, Extension = 0.71); the Visual Analog Scale (VAS) has been improved in both treatment groups with dominance for ultrasound therapy. Conclusion: Both magnetic field and ultrasound therapy effectively treat women with carpal tunnel syndrome. Magnetic field therapy was statistically superior to ultrasound.